Psicologia e relações raciais: implicações para a prática clínica - Carvalho, Cassiana Rabelo de (2025)
Race relations in Brazil are permeated by racism, a structured form of discrimination that occurs through conscious or unconscious actions, in which one group receives privileges over another. Psychology, as a science and profession, has a social responsibility in the fight against racism. Thus, this research is guided by the following question: how are racial issues considered in the training and practice of Clinical Psychology? This qualitative study involved semi-structured interviews with four Clinical Psychology professors; four clinical psychologists; and six Black individuals undergoing psychotherapy. The instruments used were three semi-structured interview guides. The interview data were analyzed using Bardin's content analysis. The results indicated that clinical psychology training has proven insufficient to promote a deep understanding of race relations, and that this impacts the work of clinical psychologists in addressing racial issues and combating racism in their practice. These limitations in training were reflected in the experiences reported by Black clients, whose main therapeutic needs were related to anxiety and depression. Conversely, the reports also indicated that psychotherapy can be a powerful space for listening and transformation when led by professionals with racial sensitivity and cultural competence. Therefore, we observed that there is an implication with race relations, but there is still room for progress in breaking with traditional and universalizing psychology.